The importance of Health Literacy in Primary Care: integrative literature review (Research, Society and Development, 2021)
Objective: to discuss, based on scientific evidence, the application and functionality of literacy in Primary Care, aiming to clearly present the development of patients, presenting the factors that make this practice so important and vector of changes in the population's health. Method: This is an integrative literature review carried out in the SCIELO, LILACS, BDENF and PUBMED (MEDLINE) databases, carried out between March and September 2021 with the descriptors Health Literacy, Primary Health Care and Health Education. The articles selected for analysis and interpretation had as criteria: original articles, published in Portuguese, English and Spanish, available free of charge, that addressed Literacy in Health and Primary Care, and that are related to the objective of this work. The exclusion criteria were: integrative literature review articles, publications prior to 2016, articles in other languages, and those that were not related to the proposed topic. 10 articles were selected, from the SCIELO and PUBMED (MEDLINE) database. Results and discussion: After analyzing the articles, the following topics were found for discussion: Literacy as a social determinant of population health; Health Literacy in Primary Care; and Development of Health Literacy. Conclusion: Inadequate health literacy can contribute to health problems and diseases of the population, and its recognition is relevant for the establishment of strategies and actions aimed at better results in the production of care.